Gênero Gomphonema Ehrenberg, 1832 (Bacillariophyceae) em igarapés e rios da Região Calha Norte (Pará, brasil): taxonomia - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
Diatoms constitute a group of algae, unicellular and multicellular, inhabit marine and continental environments, whether in fresh or brackish water and in humid terrestrial environments. The most notable groups of continental microalgae in the Amazon include diatoms (Bacillariophyta) and desmids (Chlorophyta). In the State of Pará, taxonomic studies of the genus Gomphonema are still quite scarce. Thus, this work aims to record the taxonomic composition of the species, providing information for the group in the Calha Norte region. Eight samples were collected in December 2020, three in rivers and two streams, four samples were periphytic and four planktonic. The planktonic samples were obtained with a plankton net with a mesh opening of 20 μm, through vertical and horizontal hauls. For the periphytic samples, the substrate of the colonized surface (stones and logs) was scraped with a toothbrush. After the oxidation process, the samples were mounted between 3 and 5 permanent slides, which were analyzed in optical microscopy. Nine taxa of the genus Gomphonema were identified, six identified at the specific level, two at the variety level and one at the genus level. Gomphonema parvulum var. lagenula was the taxon that presented the greatest distribution, as it occurred in all sampling points, being considered constant (C), and the remaining eight taxa presented rare and sporadic occurrence, as a genus was found in each sampling point, these are: G. affine, G. augur var. turris, G. brasiliense ssp. pacificum, G. gibberum, G. lepidum, G. pantropicum, and Gomphonema sp. 1 were rare (R). And G. pseudoaugur fell into the sporadic category (E).
Keywords: Água doce; Ambientes lóticos; América do Sul; Diatomáceas; CNPQ:: CIÊNCIAS BIOLÓGICAS